HUBUNGAN STATUS NUTRISI DENGAN DERAJAT PROTEINURIA PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN KOMPLIKASI NEFROPATI DIABETIK DI RSUP SANGLAH - I Gusti Ayu Mardewi; Ketut Suastika (E-Jurnal Medika Udayana, 2016)
There were 2,1% of Indonesian population with diabetic in 2013. Diabetic nephropathy is the most severe complication with high mortality and morbidity. In diabetic type 2 patient, microalbuminuria was irreversible and 20-40% of the patients will have proteinuria. Proteinuria related to body mass index (BMI). Higher the BMI the more severe the degree of proteinuria in patient with type 2 diabetic. The study conducted to evaluate the nutritional status of the patients and its relation with degree of proteinuria in type 2 diabetic patient with diabetic nephropathy complication. The study was analytic cross sectional study. Subjects were selected using consecutive sampling. Forty-eightsamples were match inclusion criteria, according to subjective global assessment (SGA) 31 of them listed as good nutrition (A), 11 of them suspect malnutrition (B), and 6 of them malnutrition. According to BMI, 3 patients underweight, 30 patients normal, 13 patients overweight, and 2 patients obese I. The distribution of proteinuria degrees were 2 patients negative, 10 patients +1, 12 patients +2, 13 patients +3 and 11 patients +4. The result from chi-square analysis was found, there were no significant association between nutritional statuses according BMI with proteinuria degrees (p=1.00). Also there were no significant association between nutritional status according SGA with proteinuria (p=0.46). The result was caused by some factors such as samples number, factors that affecting proteinuria, and patient’s complication.